Univariate and multivariate analysis on processing tomato quality under different mulches (Scientia Agricola, 2014)
The use of eco-friendly mulch materials as alternatives to the standard polyethylene (PE) has become increasingly prevalent worldwide. Consequently, a comparison of mulch materials from different origins is necessary to evaluate their feasibility. Several researchers have compared the effects of mulch materials on each crop variable through univariate analysis (ANOVA). However, it is important to focus on the effect of these materials on fruit quality, because this factor decisively influences the acceptance of the final product by consumers and the industrial sector. This study aimed to analyze the information supplied by a randomized complete block experiment combined over two seasons, a principal component analysis (PCA) and a cluster analysis (CA) when studying the effects of mulch materials on the quality of processing tomato (Lycopersicon esculentum Mill.). The study focused on the variability in the quality measurements and on the determination of mulch materials with a similar response to them. A comparison of the results from both types of analysis yielded complementary information. ANOVA showed the similarity of certain materials. However, considering the totality of the variables analyzed, the final interpretation was slightly complicated. PCA indicated that the juice color, the fruit firmness and the soluble solid content were the most influential factors in the total variability of a set of 12 juice and fruit variables, and CA allowed us to establish four categories of treatment: plastics (polyethylene - PE, oxo- and biodegradable materials), papers, manual weeding and barley (Hordeum vulgare L.) straw. Oxobiodegradable and PE were most closely related based on CA.